2016
DOI: 10.3382/ps/pev374
|View full text |Cite
|
Sign up to set email alerts
|

Organic trace mineral supplementation enhances local and systemic innate immune responses and modulates oxidative stress in broiler chickens

Abstract: The effect of organic trace mineral supplementation on performance, intestinal morphology, immune organ weights (bursa of Fabricius and spleen), expression of innate immune response related genes, blood heterophils/lymphocytes ratio, chemical metabolic panel, natural antibodies (IgG), and oxidative stress of broiler chickens was studied. A total of 1,080 day-old male broilers were assigned to 1 of 3 dietary treatments, which included basal diet with Monensin (control), control diet supplemented with bacitracin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 51 publications
0
31
0
1
Order By: Relevance
“…The increase in blood uric acid concentration could be associated with the free radical scavenging capacity [27]. In a previous study where broiler chickens were fed diets that replaced inorganic TM with organic TM, the authors found a signi cantly higher serum uric acid level [1]. In part, these ndings could contribute to the possible reduction of tissue damage by organically complexed minerals.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The increase in blood uric acid concentration could be associated with the free radical scavenging capacity [27]. In a previous study where broiler chickens were fed diets that replaced inorganic TM with organic TM, the authors found a signi cantly higher serum uric acid level [1]. In part, these ndings could contribute to the possible reduction of tissue damage by organically complexed minerals.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the AID of Cu was higher (P < 0.05) in the CTM25 group relative to the CTM100 group. Table 5 Effect of experimental treatments on percent ileal absorption of minerals in broilers 1 Values in the same row with different superscripts were signi cantly different (P < 0.05).…”
Section: Mineral Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Echeverry et al. () found that trace mineral supplementation enhanced local and systemic innate immune responses and modulated oxidative stress in broiler chickens. Furthermore, transcriptomic profiling indicated an enhanced immune response in Rainbow Trout that were fed selenium‐supplemented diets compared with those that were fed a basal diet (Pacitti et al.…”
Section: Resultsmentioning
confidence: 99%
“…In Vibrio alginolyticus-challenged shrimp, azomite supplementation increased survival rates (Tan et al 2014). Echeverry et al (2016) found that trace mineral supplementation enhanced local and systemic innate immune responses and modulated oxidative stress in broiler chickens. Furthermore, transcriptomic profiling indicated an enhanced immune response in Rainbow Trout that were fed selenium-supplemented diets compared with those that were fed a basal diet (Pacitti et al 2016), and the administration of mineral-enriched diets improved the disease resistance of Stinging Catfish Heteropneustes fossilis against Aeromonas hydrophila (Jawahar et al 2018).…”
mentioning
confidence: 98%